Sponsors’ Roles and Duties an Virtue and Courage Development Case Study: Saint Peter’s Church, Samphran Nakhonpathom. - Aimesattee, Nuttapon; Chumsriphun, Surachai; Kritcharoen, Apisit; Prasutsaengchan, Laddawan (Saengtham College Journal, 2021)
The research will focus on the role and duties of sponsors in the development of the virtue of courage 1) Sponsors’ role and duties to their godchildren, 2) The method that sponsors apply to develop virtue and courage in their godchildren. Research data comes from the representative sample as follows 1) Parent(s) who have children as Godchildren, age between 14-16 years old 12 people, 2) Godchildren 12 people, 3) Sponsors 12 people who attend St.Peter Church, Sampran, Nakhon Pathom province, Roman Catholic Archdiocese of Bangkok. The research uses descriptive statistics to conduct research analysis by using personal data analysis of the providers showing frequency and percentage. The result of this research reveal: 1. Sponsors fulfill the role and do their duties as sponsors of their Godchildren especially encouraging them about virtue, faith, love, hope, and courage. Sponsors encourage in love, followed by faith, courage and hope. Mostly, sponsors encourage their godchildren to have devotion and to develop to them, self-love, hope for themselves, and conscience and judgment. Sponsors encourage their Godchildren somewhat less to have hope in God and others. 2. Sponsors apply methods to encourage development in virtue and courage in their Godchildren in 9 ways as follow; 1) Sponsors need to give good examples, shown by good actions, 2)Sponsors need to teach doctrine by a good lifestyle, 3) Sponsors need to talk and have good communication to their godchildren, 4) Sponsors need to work together with their Godchildren’s families, 5) Sponsors need to be attentive and have close relationships with their Godchildren, 6) Sponsors need to have knowledge technology and social media of in order to guide their Godchildren how to use them in the right way, 7) Sponsors need to have confidence in their Godchildren and realize their value and dignity, 8) Sponsors need to encourage their godchildren to a more active and inestimable lifestyle, 9) Sponsors need to encourage and offer ongoing support to their Godchildren.